Investigation of microstructure evolution, mechanical and corrosion properties of SAF 2507 super duplex stainless steel joints by keyhole plasma arc welding - Qi Wang; Guochao Gu; Chuanbao Jia; Kan Li; Chuansong Wu (Journal of Materials Research and Technology, 2023)
Keyhole plasma arc welding (PAW) of the super duplex stainless steel (SDSS) is expected to achieve full-penetration joints of medium-thickness plates in a single pass with higher efficiency. However, the unique key-holing processes due to the special constricted arc behaviors cause much different thermal cycles of the liquid metals as well as changed microstructures. SDSS 2507 with a thickness of 10 mm was joined by PAW to investigate the joints' microstructure and properties. Microstructure characterization reveals substantial differences in the content of austenite, ranging from 68.9% in weld metal (WM) to 32.1% in the heat-affected zone (HAZ). The oxide inclusions in the WM enhance the hardness of the welded joints, but provide the path for crack propagation to decrease its impact toughness. While complicated microstructure is found in HAZ forming ferrite and diverse austenite, such as grain boundary austenite (GBA), intragrain austenite (IGA), and Widmanstätten austenites (WA). A small amount of secondary austenite (γ2) and chromium nitride are also found in HAZ, and they significantly deteriorate its corrosion resistance. The grain boundary misorientation angle distribution of the austenite in WM is found to be dominated by the low angle boundaries (LABs). However, its content decreases from the WM to base metal (BM). Selective corrosion occurs in all samples, where ferrite is preferentially dissolved when the extrinsic voltage is low (<0.5 V) and austenite is preferentially dissolved when the extrinsic voltage is high (>0.5 V), indicating the different electrochemical activity of the two phases.